If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15m + -25 = 9m + -17 Reorder the terms: -25 + 15m = 9m + -17 Reorder the terms: -25 + 15m = -17 + 9m Solving -25 + 15m = -17 + 9m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-9m' to each side of the equation. -25 + 15m + -9m = -17 + 9m + -9m Combine like terms: 15m + -9m = 6m -25 + 6m = -17 + 9m + -9m Combine like terms: 9m + -9m = 0 -25 + 6m = -17 + 0 -25 + 6m = -17 Add '25' to each side of the equation. -25 + 25 + 6m = -17 + 25 Combine like terms: -25 + 25 = 0 0 + 6m = -17 + 25 6m = -17 + 25 Combine like terms: -17 + 25 = 8 6m = 8 Divide each side by '6'. m = 1.333333333 Simplifying m = 1.333333333
| 12a-1234567890a= | | r^2-2t=13 | | 5x+(x+8)=-28-3X | | x^2+17+60=0 | | -18p=306 | | x=-x^2-10x-25 | | 6h-8=28 | | 3y+2=y+4 | | 3e+25=55 | | (2x-7)(2x+7)=0 | | (2x-7)(2x+7)=9 | | 6+4(-5+9)= | | 0=14v+14v | | 3-(2-7)= | | .333p+7=12-.666p | | x^2+4x=64 | | f(x)=(x+2) | | 4*2-6*8-7*9= | | (y^2+y-12)/(2y^2-18) | | 2i+60=80 | | ln(x)-ln(6)=3 | | 4d-7=33 | | 13e+25=8d | | -4(4y-5)+3(3y+9)= | | -5x-(2-x)=2(x-7) | | 7+21/7+7x2 | | 17r=-357 | | 7+11r-5=8r+23-4r | | m+8+6=-26 | | 7+11r-5=8r+2 | | m+8+6=26 | | y/8=117 |